V. G. Groman and the Transition to a Planned Economy in the USSR in the 1917-1930s - O. N. Kuznetsova (Научный диалог, 2019)
The question of the initial stage of the creation and functioning of a planned economy in the USSR is considered. The novelty of the study is seen in the analysis of the professional activities of the famous economist V. G. Groman, who first proposed the idea of centralized planning of the economy of Soviet Russia. The results of a study of the views of V. G. Groman are presented, with a refinement and addition of a number of facts of his biography: activities in 1917, expert work in the State Planning Commission and the board of the Central Statistical Office of the USSR. The question is raised about the fate of V. G. Groman in connection with criticism of his theory and subsequent arrest. The contribution of V. G. Groman to the scientific formulation of statistical work, as well as his socialist views, is evaluated. The question about the development of control figures as the first attempt to create an annual plan and the analysis of the “Gromanov concept” of the Soviet national economy as a whole has been raised. Attention is paid to the activities of a number of Soviet economists and to the identification of the interconnections between them and their colleagues in emigration, manifested in works and correspondence. A review of various approaches to planning and the creation of new methods and theories of planning in the works of V. G. Groman, S. G. Strumilin and S. N. Prokopovich is carried out.